Utilization of Milk Waste and Rosemary as Enviromentally Friendly Soap in Samirono, Getasan, Semarang - Palupi, Dwi Hadi Setya; Astutiningsih, Christina; Rohmah, Syifaur; Suskawati, Ida; Susilowati, Novy Dwi (Research and Social Study Institute, 2024)
Fresh cow’s milk has weaknesses, namely it is easily perishable and its shelf life tends to be short. Processing fresh cow’s milk into product is one of the efforts to extend the shelf life of cow’s milk. One of the products that can be made from fresh milk is soap. The ingredients used in making soap are quite simple and widely available in the market at relatively cheap prices. Rosemary can be used as an additive in manufacture of cow’s milk soap. The target of making envirometally friendly soap is directed at people who have dairy cows. The goal to be achieved is to increase the value of cow’s comodity and increase entrepreurship by producing and marketing enviromentally friendly soap and being able to solve the problem of relatively short milk shelf life. This service is divided into several stages. At this stage, a training process was carried out on making soap from fresh cow’s milk waste and marketing methods for the product. It is hoped that milk that can be consumed again can be processed into soap using active ingredients from rosemary, so that the soap produced can increase added value both economically and for the environment. The results of this community service is solid soap using raw materials from milk waste and rosmeray. This community service activity was received with great enthusiasm by the participants who took part in the training on how to make cow's milk soap. There is a significant difference (p<0.05) in the results of the pretest and posttest questionnaires, indicating an increase in understanding of the material presented in this community service activity. This activity has been successfully implemented.